Preservasi, Konservasi dan Renovasi Kawasan Kota Tua Jakarta - Setiawan, Budi (Bina Nusantara University, 2010)
“Great nation is a nation who’s always appreciates their own history,” that was a statement from Bung Karno. This paper is trying to lift a heritage district in Kota Tua Jakarta. A legacy that full of arts, cultures, stories, romance and tragedy that happened, and how the origin of the city formed. It’s very unfortunate if you see the condition right now. When all of the nations soo proud of their culture and history, everyone is competing to maintain and conserve their heritage and run the management very well. What happened with our heritage? Nowadays, Kota Tua district has been revitalized, but sadly, the process didn’t maintained well. So the results looks neglected and not in the good shape.